MassMin 2020: Proceedings of the Eighth International Conference &Amp; Exhibition on Mass Mining 2020
DOI: 10.36487/acg_repo/2063_0.03
|View full text |Cite
|
Sign up to set email alerts
|

PT Freeport Indonesia – The transition to underground production

Abstract: This paper will discuss the production history, current challenges and the future plans for the PT Freeport Indonesia (PTFI) minerals district as it transitions from primarily open-pit production to a series of large volume caving mines. The Grasberg open pit commenced mining in 1989 and completed at the end of 2019, having mined over 1.37 billion tonnes of ore and having produced 27 billion lbs of payable copper as well as 46 million ozs of payable gold. In addition to the ore mined, the pit also moved over 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…• Long development times before achieving planned production and associated high upfront costs: In order to achieve a high production and productivity, significant amount of infrastructure pre-development and preparatory activities, such as preconditioning or undercutting are necessary before production can commence. Consequently, the capital costs are high and the lead time, until stable production meeting the set target is achieved, is long; see for example Araneda (2020) or Casten et al (2020).…”
Section: Specific Challenges Faced In Cave Miningmentioning
confidence: 99%
“…• Long development times before achieving planned production and associated high upfront costs: In order to achieve a high production and productivity, significant amount of infrastructure pre-development and preparatory activities, such as preconditioning or undercutting are necessary before production can commence. Consequently, the capital costs are high and the lead time, until stable production meeting the set target is achieved, is long; see for example Araneda (2020) or Casten et al (2020).…”
Section: Specific Challenges Faced In Cave Miningmentioning
confidence: 99%
“…The Grasberg mining complex, operated by PT Freeport Indonesia (PTFI), is located in the southern area of Jaya Wijaya Mountains, West Papua, Indonesia. Four mines are currently operating: three caving operations at the DOZ, Deep Mill Level Zone (DMLZ) and Grasberg Block Cave (GBC) mines, and the Big Gossan stoping mine (Casten et al 2020). In addition, PTFI has several potential future operations, including the Kucing Liar and Gajah Tidur resources.…”
Section: History Of Wet Muck Spills At the Deep Ore Zone Minementioning
confidence: 99%
“…The DOZ mine is the third lift of the block cave mine in the East Ertsberg Skarn System (EESS), after the Gunung Bijih Timur (GBT) and Intermediate Ore Zone (IOZ) mines. By 2019, the DOZ mine had produced 300 million tonnes of ore since it opened in 2000 (Casten et al 2020). The extraction level is at a depth of approximately 1,200 m below the surface and includes 1,347 drawpoints across 39 panels with column heights up to 750 m. The extraction level was constructed with an offset herringbone layout to minimise wet muck flow distances.…”
Section: History Of Wet Muck Spills At the Deep Ore Zone Minementioning
confidence: 99%
“…The Deep Ore Zone (DOZ) and Deep Mill Level Zone (DMLZ) mines were developed to extract porphyry and skarn style mineralisation (copper and gold). The East Ertsberg Skarn System (EESS) hosts the orebody which has been progressively mined deeper by PT Freeport Indonesia (PTFI) since the 1980s using cave mining methods (Casten et al 2020). As such, the experiences from the DOZ and DMLZ are an excellent example of how geotechnical conditions can change with increasing mining depth, particularly with respect to strainbursting conditions.…”
Section: Case Study: the Doz And Dmlz Experiencementioning
confidence: 99%
“…The mature DOZ block cave mine will soon be decommissioned when the DMLZ cave, with a footprint approximately 500 m deeper, approaches and breaks into it. The dominant controlling geotechnical problem in the DOZ was the occurrence of inrushes of wet muck (Casten et al 2020) but strainbursts were also observed. Strainbursting in the DOZ was an irregular and localised problem, which mostly occurred when the cave was well established.…”
Section: Case Study: the Doz And Dmlz Experiencementioning
confidence: 99%